Preference Based Resource Allocation In Cloud Data Center - Dave, MR; Patel, HB; Shrimali, B (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is considered as one of the emerging technologies. Resources are allocated to users for a period of time and payment is made accordingly. Demand based preferential resource allocation is proposed which is based on the demand-supply scenario in the market. Preference based resource allocation technique allocates resources to the users based on the auction mechanism that follows market driven strategy where bid price of resources reflects the current demand. Users are discovered based on the amount capabilities. Payment is calculated based on the service preference chosen by the user. This preference is set by the Cloud Service Provider. Chosen preference decides the actual payment criteria of the winner. Time duration is divided into n time slots in order to give chance to unselected users to bid for resources in next time slot.